A construção discursiva do risco nas práticas de gestão em parcerias público-privadas: estudo de caso - Guarido, Fernanda Alves Andrade (2017)
This research aimed to explain how public values condition the relationship between risk legitimation and protection actions in the sponsored concession process of highway PR 323. We sought to understand the intersubjective construction of risks. For this, it was admitted that the risks arise from discourses, disseminated in several texts, constructed, reconstructed and consumed by the actors of the organizational field under study. It was also assumed that these discourses are capable of giving rise to actions. The theory was studied through the Public-Private Partnership case of highway PR 323. The contributions to environmental studies and organizational legitimacy lie in the development of the conception of the environment as a space for exchanges and the construction of shared understandings in this environment. With regard to legitimacy, it corroborates the understanding of the legitimation process, that is, it is assumed that legitimacy is built in the interaction between the field and wider societal spheres. Still in theoretical terms, it contributes to the understanding in the organizational studies of the Brazilian Academy of Administration, that the risks are object of the discursive dynamics of actors of the field, that legitimizes them. Thus, risk matrices that consider only legal and economic aspects neglect social phenomena of extreme importance for existence and the treatment of risks. In the context of governance studies, the contribution lies in changing the conception of the contours of the relationship between public and private actors and in the politicization and cooperation that permeate such changes. In practical terms, understanding the reasons that led to the failure of the PPP studied helps to understand the tool used and its improvement. Primary and secondary sources were selected for the research. Among them, interviews were conducted and 2,569 pages of documents composed of draft laws, laws, edicts, technical documents, political documents, actions and sentences, as well as media news were selected. Through the historical recovery of the facts, the study of the relationship between the actors of the field, the identification and interpretation of the discourses disseminated therein, texts of a political, technical and informative nature were identified. These texts have provided discourses on integrity, development, productivity and cooperation. Underlying these four was the great danger speech. Such discourses were based on public values, which justified risks, generating reactions to such dangers in the field. The legitimation of the discourse was verified by the realization of concrete actions, that is, laws were created, as structures within the state of Paraná, bidding was carried out, contract was signed, among other events. The results also showed that the field of Brazilian Public Administration is governed by regulatory, normative and cultural-cognitive bases, which give a peculiar outline to the Public-Private Partnerships developed here. It was also understood that there are public values linked to the satisfaction of citizens 'and other users' needs related to the way Public Administration works. It has been found that such public values can conflict in given situations, leading to solutions that give priority to one value, to the detriment of the other.